Density Functional Theory for QSAR Antioxidant Compound Myristicin Derivatives - Muliadi, Muliadi; Basimin, Mudzuna Quraisyah; Jayali, Ahmad Muchsin (Indonesian Journal of Chemical Research, 2021)
This research was conducted to determine the molecular structure modeling and the quantitative relationship of the activity structure (QSAR) of substituted myristicin derivatives with electron donor groups such as -C6H5 (M1), -NH2 (M2), -Cl (M3), -F (M4), and -H (M5). The results of geometry optimization with the DFT (Density Fractal Theory) method or density functional calculations calculated with the density level of B3LYP/6-31G each obtained the total energy of each compound M1- M5: M1: 175.49 kcal/mol M2: 132.707 kcal/mol, M3: 115.701 kcal/mol, M4: 116.048 kcal/mol, M5: 121.377 kcal/mol. Determining the relationship between descriptors and the antioxidant activity (IC50) for basic structure myristicin compounds and five derivatives was carried out using SPSS 21. The results of the correlation analysis showed that there was a relationship between the descriptors and antioxidant activity. Determining the best QSAR equation model is done by analyzing multiple linear and multilinear regression using IBM SPSS 21. The results of multiple linear regression analysis or multilinear regression obtained for the best QSAR equation model are: Log P = -2.600 + (0.006) IW- (1.558) qC8 - (6.532) EHOMO + (0.014) PSA + (0.133) MD with n = 6, R = 1.000, R2 = 0.926, SE = 0.